Estimation of fracture compliance from attenuation and velocity analysis of full-waveform sonic log data - Barbosa, Nicolás D.; Caspari, Eva; Rubino, Jorge German; Greenwood, Andrew; Baron, Ludovic; Holliger, Klaus (Blackwell Publishing, 2019)
Fil: Barbosa, Nicolás D.. Universite de Lausanne; Suiza. Universidad de Ginebra; Suiza